Women's perspectives on caesarean section recovery, infection and the PREPS trial: a qualitative pilot study - Annalise Weckesser; Nicola Farmer; Rinita Dam; Amie Wilson; Victoria Hodgetts Morton; R. Katie Morris (BMC, 2019)
Abstract Background In England, 27.8% of all pregnant women undergo caesarean sections (CS) to deliver their babies. Women undergoing CS are at risk of developing sepsis and post-natal infections, which not only contribute significantly to maternal mortality and morbidity, but also negatively impact upon post-natal recovery and wellbeing. This study explores patients' priorities in relation to CS recovery, focusing on their knowledge and experiences of infection prevention. The study formed part of the PREPS (Vaginal Preparation at caesarean section to Reduce Endometritis and Prevent Sepsis - a feasibility study of chlorhexidine) Trial; patients' views on the PREPS Trial were also sought. Methods Using qualitative methodology, two focus groups and six telephone interviews were carried out between September and October 2017 with a total of 21 women who had undergone a CS within the preceding six months. Focus groups and individual telephone interviews were audio-recorded and transcribed verbatim; a thematic analysis was conducted using NVivo 11. Results Women's priorities around CS recovery centred on pain (or the lack thereof), mobility and the ability to resume everyday activities, including caregiving. Those undergoing a CS for the first time reported not feeling confident in their ability to identify signs of infection and sought visiting health professionals' expertise and reassurance. Women were unable to recall whether they had received information regarding infection prevention and felt that they had not received sufficient advice. Some reported receiving general information regarding CS recovery, which ranged in quality. Prevention of womb infection is a major goal of the PREPS trial, however, the majority of women were not aware that womb (as opposed to wound) infection was a post CS risk. Conclusions Women undergoing a CS want more information on what constitutes a 'normal' post-operative recovery and specifically would welcome written information and infection prevention advice. This should be a key element of improving post-CS maternal experiences and potentially reducing sepsis and infection rates. CS stigma negatively impacts women's recovery experiences and possibly information provision. The PREPS team incorporated findings regarding consent pathways for recruiting women into intrapartum research and developed two patient reported outcomes to collect in the main trial. Trial registration The PREPS trial has been registered with ISRCTN on the 10th July 2017 (ISRCTN33435996).